Determination of mycotoxins by HPLC, LC-MS/MS and health risk assessment of the mycotoxins in bee products of Turkey - Keskin, Eda; Eyüpoğlu, Ozan Emre (NLM (Medline), 2023)
The aim of this study is to determine the levels of deoxynivalenol (DON), HT-2 toxin (HT2), T-2 toxin (T2), and ochratoxin A (OTA) in bee products (bee pollen, propolis, honey and royal jelly) available in Turkey. In addition, exposure and health risk assessments were performed to identify the potential health risk of these mycotoxins. The mycotoxins were analyzed by high-performance liquid chromatography (HPLC) with a UV detector and positive samples were confirmed with liquid chromatography-tandem mass spectrometry (LC-MS/MS). The most common mycotoxins in all bee products were DON and T-2 toxin, with mean concentrations of 1.601 and 0.704 µg/per kg dry sample, respectively, followed by OTA and HT-2 toxin. It was determined that the mycotoxins taken as a result of consuming bee products in specified amounts do not pose a risk to health.
Keywords: Bee Products; Deoxynivalenol; HPLC-UV-MS; Margin of Exposure